Addressing big data challenges in smart cities: a systematic literature review. Issue 4 (13th June 2016) - Chauhan, Sumedha; Agarwal, Neetima; Kar, Arpan Kumar
Abstract : Purpose: Big Data has become crucial for fulfilling the vision of smart cities; however, there are several challenges associated with its use. This study aims to provide a holistic view of challenges of using Big Data in smart cities and the solutions to deal with them by systematically selecting, reviewing and synthesizing the literature in this area. Design/methodology/approach: A systematic literature review was conducted by following a rigorous search protocol that identified a total of 310 peer-reviewed academic research papers. These papers were subsequently filtered and finally 38 relevant papers were selected. Findings: A number of major challenges (human dynamics, privacy, security, volume, velocity, variety, veracity and value) associated with Big Data in a smart city and the respective solutions to address them were identified. This study primarily contributes in providing the process of effectively managing Big Data in smart cities. Practical implications: The study provides valuable information to the Big Data practitioners by illustrating the process of effective management of Big Data in smart cities. This study further provides the directions to the future researchers. Originality/value: The study is original and is based on the existing literature and its interpretation.